1992
DOI: 10.1073/pnas.89.15.6958
|View full text |Cite
|
Sign up to set email alerts
|

Ethidium bromide provides a simple tool for identifying genuine DNA-independent protein associations.

Abstract: DNA-dependent and DNA-independent associations of DNA-binding proteins are important in transcriptional regulation. The analysis of DNA-independent associations frequently relies on assaying protein interaction in the absence of target DNA sequences. We have found that contaminating DNA in protein preparations can stabilize DNAdependent associations that may appear DNA-independent. Three cellular proteins of 70, 85, and 110 kDa coimmunoprecipitated with the octamer motif-binding protein Oct-2 because of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
302
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(319 citation statements)
references
References 40 publications
15
302
2
Order By: Relevance
“…Reciprocally, when endogenous Par3 was precipitated, Ku proteins were also specifically co-precipitated. Since Ku proteins are DNA-binding proteins, to exclude the possibility that DNA mediates the interaction between Par3 and Ku70/Ku80, we treated the Par3 immunoprecipitates with micrococcal nuclease, or added ethidium bromide (EB), which is known to disrupt protein-DNA interactions [20], to the lysates before performing immunoprecipitation. Our data showed that DNA did not mediate Par3-Ku association (Supplementary information, Figure S2).…”
Section: Ku70/ku80 Specifically Interacts With Par3 In Vitro and In Vivomentioning
confidence: 99%
“…Reciprocally, when endogenous Par3 was precipitated, Ku proteins were also specifically co-precipitated. Since Ku proteins are DNA-binding proteins, to exclude the possibility that DNA mediates the interaction between Par3 and Ku70/Ku80, we treated the Par3 immunoprecipitates with micrococcal nuclease, or added ethidium bromide (EB), which is known to disrupt protein-DNA interactions [20], to the lysates before performing immunoprecipitation. Our data showed that DNA did not mediate Par3-Ku association (Supplementary information, Figure S2).…”
Section: Ku70/ku80 Specifically Interacts With Par3 In Vitro and In Vivomentioning
confidence: 99%
“…5A). In addition, this specific interaction between RelA and Spl was observed in the presence of ethidium bromide (data not shown), which has been shown to disrupt DNA-dependent protein-protein interactions (37 to the zinc finger (F) region of Spl alone and showed nonspecific binding to the D domain (Fig. 5C).…”
Section: Methodsmentioning
confidence: 96%
“…Extensive PARP-1 automodification did not seem to be required for Ku binding, as addition of the PARP-1 enzymatic inhibitor 4ANI, which effectively blocked the shift in PARP-1 mobility on SDS-PAGE ( Figure 5c) and inhibited 32 P NAD incorporation by over 95% (data not shown), enhanced the coimmunoprecipitation of PARP-1 with Ku, suggesting a preferential interaction between Ku and PARP-1 before its auto-ADP ribosylation, but subsequent to DNA damage. Finally, addition of ethidium bromide to the extracts, which disrupts protein-DNA interactions (Lai and Herr, 1992), prevented coimmunoprecipitation of PARP-1 and Ku (Figure 5d). Although this result indicates that DNA contact by PARP-1 and/or Ku is important to detect their physical association, it leaves open whether the two factors are preferentially recruited to the same DNA ends or whether the DNA binding of one or both factors is required for their physical interaction.…”
Section: Resultsmentioning
confidence: 95%